Greater protein quality of an egg breakfast may be inadequate to induce satiety during weight loss, compared with a cereal breakfast of equal protein quantity. (17th November 2022) - Zhu, Yaqiong; Bailey, Dylan; Childress, Allison; Dawson, John A.; Binks, Martin; Dhurandhar, Nikhil V.
Abstract: We compared the effects of consuming egg-breakfast of superior protein quality to cereal-breakfast of similar energy density and protein quantity, but lower protein quality. Two, two-week randomised crossover clinical trials included 30 otherwise healthy women with overweight or obesity. Subjects received counselling to follow a reduced-calorie diet. Under supervision, participants consumed either breakfast for one-week then crossed over to the opposite breakfast. Experiment-1 outcome variables included post-breakfast appetite hormones, glucose and insulin, subjective markers of satiety and energy intake at lunch and dinner. In Experiment-2, an appealing food (brownies) was included in lunch. Following the breakfasts, Experiment-1 showed no significant differences in outcome variables. In Experiment-2, the egg-breakfast increased fullness ( p = 0.038), but lunch-time energy intake was not different. If these findings apply to other breakfasts, it suggests that in comparing two breakfasts with similar protein quantity, the greater protein quality of a breakfast may not be adequate to induce satiety.